Soluble urokinase receptor and mortality in kidney transplant recipients - Morath, Christian; Hayek, Salim; Döhler, Bernd; Nußhag, Christian; Sommerer, Claudia; Zeier, Martin; Reiser, Jochen; Süsal, Caner (Transplant international, 2022)
Main problem: Soluble urokinase plasminogen activator receptor (suPAR) is an immunological risk factor for kidney disease and a prognostic marker for cardiovascular events. Methods: We measured serum suPAR levels in a total of 1,023 kidney transplant recipients either before (cohort 1, n=474) or at year 1 after transplantation (cohort 2, n=549). The association of suPAR levels and all-cause and cardiovascular mortality was evaluated by multivariable Cox regression analysis. Results: The highest suPAR tertile compared to the two lower tertiles had a significantly higher risk of all-cause mortality in both cohorts separately (cohort 1: hazard ratio (HR) 1.92, 95% confidence interval (CI) 1.20-3.08, P=0.007; cohort 2: HR=2.78, 95% CI 1.51-5.13, P=0.001) and combined (n=1,023, combined HR=2.14, 95% CI 1.48-3.08, P<0.001). The association remained significant in the subgroup of patients with normal kidney function (cohort 2: HR=5.40, 95% CI 1.42-20.5, P=0.013). The increased mortality risk in patients with high suPAR levels was attributable mainly to an increased rate of cardiovascular death (n=1,023, HR=4.24, 95% CI 1.81-9.96, P<0.001). Conclusions: A high suPAR level prior to and at 1 year after kidney transplantation was associated with an increased risk of patient death independent of kidney function, predominantly from cardiovascular cause.
Gesehen am 01.03.2022